The impact of modern geographic information systems (GIS) on improving the energy efficiency of maritime transportation - Anna A. Ananeva; Maksim E. Stepanov; Oleksandr A. Korostin; Maria S. Korneva (International Journal of Advanced Studies)
Background. Modern maritime transportation faces challenges related to the need for increased energy efficiency and reduced greenhouse gas emissions. These issues have become particularly relevant in the context of global environmental policies and the tightening of international ship energy efficiency standards (EEDI, EEOI, CII). One of the promising solutions is the use of geographic information systems (GIS), which enable vessel route optimization, reduce fuel consumption, and minimize environmental impact. However, the extent of their impact on improving maritime transport energy efficiency requires further research.